2008
DOI: 10.1631/jzus.b0710625
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on the teratogenesis of dexamethasone and the preventive effect of vitamin B12 on murine embryonic palatal shelf fusion in vitro

Abstract: Excessive dexamethasone (Dex) administrated into pregnant mice during critical periods of palatal development can produce a high incidence of cleft palate. Its mechanisms remain unknown. Vitamin B 12 has been shown to antagonize the teratogenic effects of Dex, which, however, remains controversial. In this study, we investigated the effects of Dex and vitamin B 12 on murine embryonic palatal shelf fusion using organ culture of murine embryonic shelves. The explanted palatal shelves on embryonic day 14 (E14) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Mouse palatal shelf culture was carried out according to our previous study [Lu et al, 2008]. Palatal shelves of C57BL/6J mouse embryos were removed by using microsurgical shears and forceps under a dissecting microscope, and placed on 0.4‐µm porosity Millipore filters (Millipore Corporation, Carrigtwohill, Ireland) in 35‐mm tissue culture dishes.…”
Section: Methodsmentioning
confidence: 99%
“…Mouse palatal shelf culture was carried out according to our previous study [Lu et al, 2008]. Palatal shelves of C57BL/6J mouse embryos were removed by using microsurgical shears and forceps under a dissecting microscope, and placed on 0.4‐µm porosity Millipore filters (Millipore Corporation, Carrigtwohill, Ireland) in 35‐mm tissue culture dishes.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies also demonstrated that vitamin B 12 effectively restored DEX-induced failure of the palatal fusion in mice embryos (Lu et al, 2008). In our current study, we found that there was no significant difference in the palatal cleft incidence in Groups B and C (Table 1), and the size of palate between the two groups also had no distinguished difference.…”
Section: Discussionmentioning
confidence: 73%
“…Vitamin B 12 is one of the diverse vitamin B family members, which has extensively antagonistic effects on developmental toxicity and teratogenesis. Lu et al (2008) revealed that vitamin B 12 could effectively antagonize DEX-induced failure of the palatal fusion in mice embryos. However, an effect of vitamin B 12 on the combined toxicity of TCDD and DEX for palatal development has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Dex-induced cleft palates in mice have become a standard animal model of cleft palate etiology and an important tool for studying pathogenesis and treatment (Dudas et al 2004;Martinez-Alvarez et al 2004;Xu et al 2009). Some studies have shown that B 12 antagonizes the teratogenic effects of Dex on palate fusion in mouse embryos in vitro using the organ culture method (Hassell 1975;Lu et al 2008); another paper revealed the same effects of B 12 in a stereomicroscope study (He et al 2009). While it seems clear that B 12 antagonizes the effects of Dex, its mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 94%